Design of CPW antenna for network applications - Sanmugasundaram, R.; Dileepan, D.; Natarajan, S. (International Journal of Engineering and Technology, 2018)
The novel CPW antenna design consists of monopole, which can used for High speed wide area or local area corporate networks and Video & CCTV surveillance networks and Long-range Rural connectivity. This antenna has been designed with design size parameters of 59.5(L) x 30 (W) x 1.6-(H) mm2, the dielectric constant of FR4 substrate is 4.4, and loss tangent of 0.002 is used. The resonant frequency range of this proposed antenna is 5.85 - 6.6 GHz with return loss above of -10dB achieved. The peak gain of this antenna is 5.5dBi and in addition the S, Z-parameters, VSWR, 2D & 3D radiation pattern are also derived. Good results are achieved after simulation.Â Â